AQPETKEY ARXIPELAGI TUPROQ MAKROFAUNASI DOMINANT TURLARINING BIOEKOLOGIYASI - Jumanov , M.A.; Isayev , R.T; Alimbetov , A.A; Aseminova, D.Y.; Tajetdinov , M.M.; Ubaydullayeva, E.A; Ilyasova , G.J.; Matmuratov , M.A. (Actual problems and prospects of the study of the fauna, 2024)
The water of the Aral Sea has completely dried up as a result of changes in the natural conditions of the world, that is, an increase in global temperature on the earth's continent, as well as the influence of anthropogenic transformative factors. At this location, in the eastern Aral Sea, the Akbetkey archipelago consists of approximately 50 islands. The land resource of the archipelago is mainly the sand dunes of the Kyzylkum Desert, and today it is covered with saline, gypsum and sandy black soils, which are known to have caused major changes in the area. Identification of the dominant species in the macrofauna of the Akbetkey archipelago in the eastern part of the Aral Sea and the study of bioecological features.